Book Review of "Neighbours in Arms: An American Senator’s Quest for Disarmament in a Nuclear Subcontinent" by Larry Pressler - Gulshan Bibi (International Journal of Nuclear Security, 2018)
As chairman of the US Senate s Arms Control Subcommittee, Larry Pressler advocated the now-famous Pressler Amendment, enforced in 1990. Aid and military sales to Pakistan were blocked, including a consignment of F-16 fighter aircraft, changing forever the tenor of the United States relationships with Pakistan and India, and making Pressler a temporary hero throughout India and a devil in Pakistan . This book reveals what went on behind the scenes in the years when the Pressler Amendment was in force, through a cast of characters that include presidents, prime ministers, senators and generals in the US, India and Pakistan. It exposes the enormous power wielded by the military-industrial complex, which the author terms Octopus , and how it controls significant aspects of the American presence in the Indian subcontinent.